2015
DOI: 10.1007/s11882-014-0509-6
|View full text |Cite
|
Sign up to set email alerts
|

The Asthma COPD Overlap Syndrome (ACOS)

Abstract: Asthma and chronic obstructive pulmonary disease (COPD) have traditionally been viewed as distinct clinical entities. Recently, however, much attention has been focused on patients with overlapping features of both asthma and COPD: those with asthma COPD overlap syndrome (ACOS). Although no universal definition criteria exist, recent publications attempted to define patients with ACOS based on differences in clinical features, radiographic findings, and diagnostic tests. Patients with ACOS make up a large perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 82 publications
1
44
0
7
Order By: Relevance
“…Az irodalomban elérhető adatok alapján számos kritéri-umrendszert használnak az ACOS definíciójának meghatározásához [54]. A GINA-GOLD dokumentumokban megfogalmazott új definíció alapján az ACOS olyan változó karakterisztikájú légúti áramláskorlátozottsággal jellemzett kórkép, amelynek tulajdonságai általában az asthma és a COPD jellemzőivel párosulnak.…”
Section: Definíció éS Diagnosztikai Megfontolásokunclassified
“…Az irodalomban elérhető adatok alapján számos kritéri-umrendszert használnak az ACOS definíciójának meghatározásához [54]. A GINA-GOLD dokumentumokban megfogalmazott új definíció alapján az ACOS olyan változó karakterisztikájú légúti áramláskorlátozottsággal jellemzett kórkép, amelynek tulajdonságai általában az asthma és a COPD jellemzőivel párosulnak.…”
Section: Definíció éS Diagnosztikai Megfontolásokunclassified
“…It is difficult to clinically distinguish COPD from asthma, and therefore these diagnoses often overlap (asthma-COPD overlap syndrome). In previous research showed the prevalence of asthma-COPD overlap syndrome was 1.8-56.0% [25][26][27][28]. Therefore, we did not remove patients with asthma from the study population.…”
Section: Comparison With Similar Studiesmentioning
confidence: 99%
“…Recently, a combination of these two diseases, the so-called asthma-COPD intersection (ACP), characterized by more expressed symptoms, frequent exacerbations and worse prognosis in comparison with two pathologies separately [1,2].…”
Section: Introductionmentioning
confidence: 99%